Effectiveness of TITANICS (Three-Dimensions Interactive Animation of Thermodynamics) Learning Media to Improve Students’ Cognitive Learning Outcomes - Arrahmat, Mohamad Wahdiansyah; Anggaryani, Mita; Saputra, Oka; Jatmiko, Budi; Citra, Nina Fajriyah (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective: This study aims to describe the effectiveness of the development of TITANICS media (Three-Dimensional Interactive Animation of Thermodynamics) in improving students’ cognitive learning outcomes. This is based on the need for future innovative learning strategies that integrate digital technology into educational institutions. Method: This research uses a development approach using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The sample consisted of 28 students from class XI Science 1 at Trensains Tebuireng High School, selected through purposive sampling. Results:Based on the data and analysis conducted, it can be concluded that the TITANICS learning media (Three-Dimensional Interactive Animation of Thermodynamics) is effective in improving students’ cognitive learning outcomes in thermodynamics. Novelty: This study presents the development of digital media featuring 3D animation, formed into interactive videos that include educational content and quiz questions contextualized with real-life applications of thermodynamic concepts.